Effect of tobacco use on disease activity and DMT discontinuation in multiple sclerosis patients treated with dimethyl fumarate or fingolimod. Issue 4 (September 2020) - Hersh, Carrie M; Harris, Haleigh; Ayers, Malissa; Conway, Devon
Background: Tobacco exposure is a modifiable risk factor for multiple sclerosis (MS). Studies evaluating the relationship between tobacco, disease activity, and disease modifying therapy (DMT) persistence yielded conflicting results. We sought to address this issue with data from clinical practice. Objective: To compare 24-month disease outcomes in tobacco versus non-tobacco users treated with dimethyl fumarate (DMF) or fingolimod (FTY) in clinical practice. Methods: We retrospectively identified 659 MS patients treated with DMF or FTY, stratified by patient-reported tobacco use. DMT discontinuation and measures of disease activity at 24 months were assessed using propensity score (PS) weighting. Outcome estimates were calculated as tobacco vs non-tobacco use. Results: 164 tobacco users (DMF n = 101; FTY n = 63) and 495 non-tobacco users (DMF n = 294; FTY n = 201) were identified. Tobacco (39.4%) and non-tobacco (34.4%) users were equally likely to discontinue DMT (OR = 1.17, 95% CI 0.79, 1.75), but tobacco users discontinued therapy earlier (HR = 1.53, 95% CI 1.06, 2.43). There were no differences in ARR (rate ratio = 1.39, 95% CI 0.97, 1.96). However, tobacco users had decreased odds of NEDA-2 (OR = 0.61, 95% CI 0.44, 0.83). Conclusion: Our findings suggest that tobacco is a negative risk factor for inflammatory disease activity and earlier DMF and FTY discontinuation.